Physicochemical and mechanical properties of self consolidating lightweight foamed concrete containing recycled concrete aggregate / Mohd Afiq Mohd Fauzi - Mohd Fauzi, Mohd Afiq (2023)
Recycling waste materials began decades ago. However, the continuous use of recycled materials has only recently begun. Not left behind in the recycling current is the concrete material. Generally, tonnes of Construction and Demolition Wastes (C&DW) are raised daily. The situation is similar to the cement industry where a large amount of cement is generated every day and at the same time will affect the environment due to the carbon dioxide emission during the production of the cement and devastating harmful impact on the surroundings. For these reasons, there are two main reasons for the rationale for recycling concrete waste as aggregate, the first is the need to save natural aggregate resources that will be reduced in the future, and the second is to address the problem of waste disposal and preserve the environment. Acceptance of the use of concrete waste as an aggregate source is limited if the question of its strength and durability is not ascertained. Hence, an effort made in this regard is the development of Self-Consolidating Lightweight Foamed Concrete (SCLFC). SCLFC is a novel material that involves innovation in the production and casting of concrete. It is a type of concrete that might not require vibration for placing it and could be produced by reducing the density of concrete.